Takhrij and Syarah Hadith of Chemistry: The Study of Integration of Islamic Character Values with Chemistry in Carbon Chemistry - Qurotul Aeni; Muhamad Azhan Azhari; Asep Supriadin; Dody S Truna; Abdul Syukur (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadiths about Muslims and other Muslims with a philosophical approach to carbon chemistry. The study of Islamic character values ​​contained in carbon chemistry has been carried out by exploring the philosophical charges in the material, the specificity of carbon atoms, bonds in carbon compounds, classification, and reactions in carbon compounds. This study integrates Islamic character values ​​to reinforce and reinforce the main ideas raised in carbon chemistry. The methods used are takhrij and sharah hadith which use content analysis techniques, analysis with a philosophical approach, analysis with a triadic model, and analysis with confirmation patterns. The results obtained from this study are: (1) remembrance of Allah SWT in the specificity of the carbon atom with 4 valence electrons; (2) maintaining the relationship of the patentable properties of the carbon atom; (3) happy to give charity and help from carbon chemical bonds; (4) be wise and fair when encountering differences in the classification of carbon compounds; (5) improve themselves and leave things that are not useful from the substitution reaction; (6) sincere in helping others from addiction reactions; and (7) patience and surrender to Allah SWT from the reaction of elimination. This study concludes that the concepts that apply in carbon compounds can be related to the values ​​of Islamic character education based on takhrij and sharah hadith with a carbon chemistry approach.